A new map to understand deubiquitination. (19th January 2010) - Katz, Elijah J.; Isasa, Marta; Crosas, Bernat
Abstract : Deubiquitination is a crucial mechanism in ubiquitin-mediated signalling networks. The importance of Dubs (deubiquitinating enzymes) as regulators of diverse cellular processes is becoming ever clearer as new roles are elucidated and new pathways are shown to be affected by this mechanism. Recent work, reviewed in the present paper, provides new perspective on the widening influence of Dubs and a new tool to focus studies of not only Dub interactions, but also potentially many more cellular systems.